2017
DOI: 10.1142/s0217751x1750049x
|View full text |Cite
|
Sign up to set email alerts
|

Discreteness of time in the evolution of the universe

Abstract: In this paper, we will first derive the Wheeler-DeWitt equation for the generalized geometry which occurs in M-theory. Then we will observe that M2-branes act as probes for this generalized geometry, and as M2-branes have an extended structure, their extended structure will limits the resolution to which this generalized geometry can be defined. We will demonstrate that this will deform the Wheeler-DeWitt equation for the generalized geometry. We analyse such a deformed Wheeler-DeWitt equation in the minisuper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…This is the main reason for the description of string theory below the length l s = α ′ being equivalent to its description above l s = α ′ . As the double field theory is constructed using T-duality [29,30], such a short distance behavior for double field theory has also been studied [36].…”
Section: Black Holes Modified From T-dualitymentioning
confidence: 99%

Black Remnants from T-Duality

Pourhassan,
Wani,
Faizal
2019
Preprint
Self Cite
“…This is the main reason for the description of string theory below the length l s = α ′ being equivalent to its description above l s = α ′ . As the double field theory is constructed using T-duality [29,30], such a short distance behavior for double field theory has also been studied [36].…”
Section: Black Holes Modified From T-dualitymentioning
confidence: 99%

Black Remnants from T-Duality

Pourhassan,
Wani,
Faizal
2019
Preprint
Self Cite
“…It may be noted as the double field theory is constructed using the T-duality [11,12], it is expected that a such zero point length can also occur in the double field theory. It has been demonstrated that such a zero point length in double field theory can have important consequences for the generalized geometries used in string theory [13]. It may be noted that such a minimal length larger than the Planck length can make it possible for the mini black holes to form in particle physics colliders (due to the lowering of Planck scale) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Then all other cuts with s 2 are on the next sheets. For the above case (11), (12), with N = 2, ǫ = 1/2, the next "kinematical" cut from the point E = −(8β) −1 (for small β) lies far away from the origin on the first sheet (for β > 0). Besides, it is screened by physical cut for β < 0.…”
mentioning
confidence: 95%
“…It should be noted that an effective path integral of the center of mass of the string (for strings propagating in compactified extra dimensions) has been constructed, and T-duality has been used to demonstrate that such a system has a minimal length associated with it [7,8]. As the construction of double field theory has been motivated from T-duality [9, 10], it is expected that such a minimal length will also exist in the double field theory [11].It may be noted that even if the string theory does not turn to be the true theory of quantum gravity, the argument for the existence of a minimal measurable length in spacetime could still hold. As it can be argued, a minimal measurable length scale, at least of the order of Planck length, would exist in all approaches to quantum gravity.…”
mentioning
confidence: 99%
See 1 more Smart Citation